2020
DOI: 10.1073/pnas.1918473117
|View full text |Cite
|
Sign up to set email alerts
|

Sensory cilia as the Achilles heel of nematodes when attacked by carnivorous mushrooms

Abstract: Fungal predatory behavior on nematodes has evolved independently in all major fungal lineages. The basidiomycete oyster mushroomPleurotus ostreatusis a carnivorous fungus that preys on nematodes to supplement its nitrogen intake under nutrient-limiting conditions. Its hyphae can paralyze nematodes within a few minutes of contact, but the mechanism had remained unclear. We demonstrate that the predator–prey relationship is highly conserved between multiplePleurotusspecies and a diversity of nematodes. To furthe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
23
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
4
2
2

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 56 publications
(52 reference statements)
4
23
0
Order By: Relevance
“…We further discovered that ss2 and ss5 exhibited differences in toxicity towards the nematode Caenorhabditis elegans. All nematodes in contact with the mycelium of ss5 were paralyzed after 10 minutes exposed to the fungal hyphae, which was comparable to previous studies of Pleurotus species (Thorn and Barron 1984;Lee et al 2020). In contrast, the mycelium of ss2 showed a much weaker toxicity toward C. elegans, being able to paralyze only ~40% of the nematode population tested ( Figure 1B).…”
Section: Phenotypic Differences Between the Two Meiotic Progeny Of A supporting
confidence: 86%
See 1 more Smart Citation
“…We further discovered that ss2 and ss5 exhibited differences in toxicity towards the nematode Caenorhabditis elegans. All nematodes in contact with the mycelium of ss5 were paralyzed after 10 minutes exposed to the fungal hyphae, which was comparable to previous studies of Pleurotus species (Thorn and Barron 1984;Lee et al 2020). In contrast, the mycelium of ss2 showed a much weaker toxicity toward C. elegans, being able to paralyze only ~40% of the nematode population tested ( Figure 1B).…”
Section: Phenotypic Differences Between the Two Meiotic Progeny Of A supporting
confidence: 86%
“…One of the most unknown characteristics of Pleurotus mushrooms is their ability to kill and feed on living nematodes (Thorn and Barron 1984) and therefore their potential for the biocontrol of parasitic nematodes (Degenkolb and Vilcinskas 2016; Sivanandhan et al 2017;Castañeda-Ramírez et al 2020). Although a few compounds produced by Pleurotus have been reported to cause paralysis in nematode worms (Kwok et al 1992;Satou et al 2008), a more recent study has suggested that the true identity of the toxins targeting nematodes remain to be discovered (Lee et al 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Single-nucleotide polymorphism mapping and whole-genome sequencing revealed nine independent, loss-of-function mutations in genes, all of which are essential for the development of ciliated sensory neurons or amphid channel morphogenesis, the latter representing the nose of the worm, the most crucial sensory organ of these blind creatures. Using these mutants along with previously established lines with known defects in either the function of ciliated sensory neurons or impaired signaling, Lee et al (7) surprisingly found that the intact cilia structure, but not sensory neural function, is needed to elicit paralysis. However, mutants with defects in ciliated sensory neuron development displayed a range of paralysis upon hyphae contact, suggesting that several factors are at play.…”
Section: Intact Cilia Of Head Sensory Neurons Needed For Instantaneoumentioning
confidence: 99%
“…Other fungi use infective spores that either bind to the nematode cuticle or are ingested (6). As explored in PNAS by Lee et al (7), the eatable oyster mushroom Pleurotus ostreatus of the Basidiomycota uses yet another mechanism by employing toxin-induced paralysis to kill its prey. While the predatory capacities of fungi are well established, the execution mechanisms are gradually being elucidated.…”
mentioning
confidence: 99%
“…Another potential toxin, linoleic acid, reduces nematodes head size (Satou et al 2008). When nematodes contact the mycelium of P. ostreatus, fungal toxins enter the prey through their sensory cilia, leading to hypercontraction and calcium influx of pharyngeal and body wall muscles, ultimately causing necrosis process of the neuromuscular system (Lee et al 2020). However, the identity of the toxins and how exactly P. ostreatus induces rapid cell necrosis remain unclear.…”
Section: Introductionmentioning
confidence: 99%